Answers

2014-04-05T10:51:25+05:30
Solution

Given a and b are odd numbers

we can define b in terms of as
b = a - 2d
here a- 2d because a>b
d= any constant
( example if a = 27 and b = 21 then the d = 3 ie 2d=6 )
the difference any two odd positive number is always even .


now 1)  a + b / 2
           = ( a + (a - 2d ) ) /2
           = (2a - 2d ) /2
           =( even number ) /2
           = even

     2) a - b / 2
           = ( a - (a - 2d ) ) / 2
           = ( 2d ) /2
           =  d
           = odd
d = 2d  / 2
and d is always odd
( eg a=501 and b = 251
       2d = 250
         d = 125 which is odd)

3 3 3